What keeps Islamic mobile banking customers loyal? - Mohd Thas Thaker, Mohamed Asmy; Amin, Md Fouad; Mohd Thas Thaker, Hassanudin; Allah Pitchay, Anwar (Emerald Group Publishing Limited, 2019)
Purpose – This study aims to find important factors of Malaysian Islamic banking customers’ loyalty or continuance intention to use Islamic mobile banking services. Design/methodology/approach – The primary data are collected from the survey administered to 250 customers in the Klang Valley and the analysis is conducted using partial least squares (PLS). Findings – Based on the findings, continuance intention of using Islamic mobile banking services was found to be depended on the usability of mobile banking services, customer service provided by Islamic banks towards mobile banking services, customer satisfaction on mobile banking services and trust of customers towards mobile banking services. In addition, the mediating effect of Islamic mobile banking services continuance adoption is significantly influenced by customer satisfaction and trust. Research limitations/implications – The sample size and area of study become the obvious limitations, and interpretation of the results and conclusion cannot be as generalised. In addition, as the respondents of this study are existing customers who have used Islamic mobile banking services at least once, relying on the perception of one key informant might imply cognitive biases. Besides, the use of current factors might limit the ability to explore other potentially important determinants of the customers’ continuance intention in using Islamic mobile banking services. Practical implications – By understanding these continuance intention factors amongst the customers, it would help the industry player particularly Islamic banking to plan and strategise appropriate policies and support necessary programmes on diversifying and promoting financial transaction using mobile banking services amongst their existing and potential customers. Originality/value – This paper offers an additional literature on Islamic mobile banking, especially from the Malaysian context. There is a lack of study that focuses on loyalty towards Islamic mobile banking services. The paper is considered to be the first attempt to examine the factors that influence Malaysian Islamic banking customers’ loyalty or continuance intention to use Islamic mobile banking services.